The Effect of Radioiodine Treatment on TRAb, Anti-TPO, and Anti-TG in Graves' Disease - Lindgren, Ola (Eur Thyroid J, 2019)
BACKGROUND: In Graves' disease (GD), immunocompetent cells infiltrate thyroid tissue with release of TSH-receptor antibodies (TRAb), and radioiodine treatment is known to elicit an immune response with an increase in TRAb. OBJECTIVES: The aim was to study if all patients treated with radioiodine respond with a release of TRAb, anti-thyroperoxidase (anti-TPO), and anti-thyroglobulin (anti-TG). METHODS: This is a prospective observational study. GD patients (n = 131) were admitted for treatment with radioiodine. Thyroid antibodies were measured before and 3 months after iodine-131 treatment. RESULTS: After 3 months, a fold change > 1.1 was found in 66% of the GD patients, while the remaining 34% did not have a change or decrease in in TRAb. Anti-TPO and anti-TG also increased; the former showed an increase in 73% and the latter of 52%, while 27 and 48% decreased/were unchanged. A significant positive correlation was found between TRAb and anti-TPO, but not between TRAb and anti-TG. In the group with an increase in TRAb, the median fold change was 5.1, but there were no additional effects of tobacco smoking. The proportion of females below the median age (51.5 years) was significantly higher in the group that increased in TRAb compared to the one that decreased/was unchanged (66 vs. 34%). CONCLUSIONS: Treatment with radioiodine elicits an increase in thyroid antibodies, but not in all GD patients. The proportion of responders varied and was affected by age, resulting in a stronger immune response at younger age. However, there were no additional effects of smoking.